Board Diversity and Managerial Control as Predictors of Corporate Social Performance - Coffey, Betty S. (Journal of business ethics, 1998)
While it is widely assumed that greater diversity in corporate governance will enhance a firm’s corporate social performance, this study considers an alternative thesis which relates managerial control to corporate philanthropy. The study empirically evaluates both board diversity and managerial control of the board as possible predictors of corporate philanthropy. The demonstration of a positive relationship between managerial control and corporate philanthropy contributes to our understanding that corporate social performance results from a complex set of economic and social motives. Possible future research and managerial implications are discussed.